Evolution of integrated solid waste management systems in brazilian cities under the national solid waste policy - Mendez, Gabriel de Pinna; Mahler, Claudio Fernando (Ciência e Natura, 2018)
This article analyzes the evolution of integrated solid waste management systems in small and medium cities of the state of Rio de Janeiro. For this purpose, we applied the Modified Solid Waste Management Condition Index (ICGRm), calculated by a spreadsheet with 40 environmental indicators. A field study was carried out to evaluate ten cities in the state of Rio de Janeiro, among twenty already investigated in a survey carried out in the years 2007-2008. The cities were classified as adequate or inadequate according to the ICGRm scores (range from zero to ten points). The comparative evaluation revealed that four cities presented positive evolution, but only slight, while six cities presented worse scores. In the specific case of Brazil, it shows that public managers have not yet given proper priority to solid waste management, although six years have passed since the establishment of the National Solid Waste Policy through Law 12,305/2010. Ten of the cities evaluated reached the level of management considered adequate by the applied method, either in the evaluation in 2007-2008 or 2016, and some showed slight improvement.